Legal Protection of Staycation Victims (Women Workers) In A Criminological Perspective) - Adhalia Septia Saputri (PT Publikasiku Academic Solution, 2023)
Staycation or vacation at home is increasingly in demand by many people, including female workers. However, this does not guarantee safety during the staycation. There is a risk of crimes such as sexual harassment that can occur. Therefore, legal protection for staycation victims needs to be considered, especially for female workers. This article discusses the legal protection of staycation victims (female workers) in criminological theories such as sociological theory, psychological theory, environmental theory, social control theory, and deterrence theory, as well as a focus on feminist criminology. These theories can help understand the causes of crimes against female workers in staycation environments and provide solutions for better legal protection for victims. Therefore, it is important to develop policies and regulations governing staycations so that female workers can feel safer when carrying out these activities. In conclusion, legal protection of staycation victims (female workers) requires cooperation between the community, security forces, government, and hotel staff in Creating a safe and comfortable environment for staycations conducted by female workers. The research used in this journal is juridical research normative.